2021
DOI: 10.3389/fonc.2020.618472
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA UCA1 Is Related to Autophagy and Apoptosis in Endometrial Stromal Cells

Abstract: Research QuestionThe expression of the long noncoding RNA (lncRNA) urothelial carcinoma-associated 1 (UCA1) in embryonic tissues is higher than that in most cancer tissues, such as bladder cancer, indicating that RNA is a carcinoembryonic antigen. However, there are no published reports on the role of UCA1 in endometriosis (EMS). Therefore, to address this gap in knowledge, we assessed the potential role of lncRNA UCA1 in the pathogenesis and progression of EMS.DesignTo verify the expression of UCA1 in EMS, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Through analyzing the RIP-seq dataset and GEO database,we identified UCA1 as an interaction partner of IGF2BP3, which was initially recognized as a promoter of bladder cancer (Li et al 2015 ). Liu et al have confirmed that UCA1 promoted the proliferation of eESCs, while inhibiting autophagy and apoptosis (Jiang et al 2020 ). Subcellular localization is a crucial factor in determining the biological function of lncRNAs.…”
Section: Discussionmentioning
confidence: 94%
“…Through analyzing the RIP-seq dataset and GEO database,we identified UCA1 as an interaction partner of IGF2BP3, which was initially recognized as a promoter of bladder cancer (Li et al 2015 ). Liu et al have confirmed that UCA1 promoted the proliferation of eESCs, while inhibiting autophagy and apoptosis (Jiang et al 2020 ). Subcellular localization is a crucial factor in determining the biological function of lncRNAs.…”
Section: Discussionmentioning
confidence: 94%
“…It is known that UCA1 may be involved in the occurrence and development of endometriosis by promoting cell proliferation and inhibiting apoptosis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to literature, the formation and maintenance of ectopic endometrial lesions at ectopic sites are the most basic characteristics of endometriosis and are strongly correlated with the pathology and pathogenesis, such as inflammation, oxidative stress, proliferation, apoptosis, angiogenesis, immunity, invasion, and adhesion. 42–47 It has also been found that some other factors, such as hormones, heredity, and environment, are implicated in the formation and/or advancement of this disease. Local estrogen augmentation and progesterone resistance are observed in endometriosis, thus promoting the survival, migration, proliferation, and adhesion of ectopic endometrial cells.…”
Section: Pathogenesis Of Endometriosismentioning
confidence: 99%
“…Endometriosis is a proliferative chronic disorder that is mainly characterized by the abnormal endometrial growth at ectopic sites outside the uterine cavity. 42 Previous studies have shown an incremental cell proliferation rate of ectopic endometrium in endometriotic patients, which is conductive to survival and implantation into the ectopic site. 50 Proliferating cell nuclear antigen (PCNA), a sensitive indicator of proliferation and DNA restoration, exists in the G1, S and G2 phases of the cell cycle, while Ki-67 exists in all active phases and is a more specific proliferative marker than PCNA.…”
Section: Molecular Mechanisms Of Resveratrol Against Endometriosismentioning
confidence: 99%
See 1 more Smart Citation